Profile of Neuron-Specific Enolase, Lactate Dehydrogenase, Fine Needle Aspiration Biopsy, and Bone Marrow Aspiration Examination to Diagnose Neuroblastoma Patients in Hematology Oncology Division of Pediatric Department at Dr. Soetomo General Hospital - Mutiani, Faradillah; Ugrasena, I Dewa Gede; Soedewo, Fery Hudowo (National Cancer Center - Dharmais Cancer Hospital, 2018)
Background: Neuroblastoma is a malignant solid tumour in children which attacks sympathetic nervous system. Despite of increment in its number of incidence, it is still rarely investigated. This research aims to improve the understanding of neuroblastoma based on the profile of patients, and further, to improve services for patients.Methods: This was a retrospective study conducted by assessing and descriptively analyzed patients medical record.Results: From 52 patients, 56% were male and 71% were between age of 1-5 years. Neuron Specific Enolase (NSE) examination showed that most patients had high levels in 29 patients (56%) while Lactate Dehydrogenase (LDH) examination showed that 23 patients (44%) had low levels. Based on Fine Needle Aspiration Biopsy (FNAB) examination, 22 patients (42%) showed formation of malignant round cell tumor. Meanwhile, through Bone Marrow Aspiration (BMA) examination, it was found that the tumors had already spread to bone marrow in 17 patients (33%).Conclusions: Based on tumor markers and pathological finding, this study revealed that the majority of neuroblastoma patients had poor prognosis.